2023
DOI: 10.1007/s11250-023-03524-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of natural betaine supplementation on rumen fermentation and productive performance of lactating Damascus goats

Abstract: Two natural betaine sources; dehydrated condensed molasses fermentation solubles (Bet1) and Betafin®, a commercial anhydrous betaine extracted from sugar beet molasses and vinasses (Bet2); were used to investigate their impact on rumen fermentation parameters and lactation performance of lactating goats. Thirty-three lactating Damascus goats, with an average weight of 37 ± 0.7 kg and their age ranged from 22 to 30 months (2nd and 3rd lactation season), were divided into three groups, each group contained 11 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…However, there was no effect of BET supplementation on total protein, glucose, and urea-N and creatinine concentrations in Aberdeen Angus cows. In agreement with the present results, no effect was observed in TP and glucose concentrations (Ghoneem and El-Tanany, 2023), urea-N (Parker et al, 2007) and creatinine (Fernández et al, 2009). The decrease in serum cholesterol concentrations may be explained by increased lipid mobilization which may confirm the role of BET as a methyl donor (Davidson et al, 2008).…”
Section: Metabolic and Biochemical Parameterssupporting
confidence: 93%
See 1 more Smart Citation
“…However, there was no effect of BET supplementation on total protein, glucose, and urea-N and creatinine concentrations in Aberdeen Angus cows. In agreement with the present results, no effect was observed in TP and glucose concentrations (Ghoneem and El-Tanany, 2023), urea-N (Parker et al, 2007) and creatinine (Fernández et al, 2009). The decrease in serum cholesterol concentrations may be explained by increased lipid mobilization which may confirm the role of BET as a methyl donor (Davidson et al, 2008).…”
Section: Metabolic and Biochemical Parameterssupporting
confidence: 93%
“…Betaine, tri-methylglycine is a recent compound found to ameliorate HS in cows (Kassab et al, 2021;Williams et al, 2021, andKondiba et al, 2023), buffalo (Shankhpal et al, 2019;Deshpande et al, 2020;Shakkarpude et al, 2022, andHussain et al, 2023), goat (Ghoneem and El-Tanany., 2023), sheep (Tsiplakou1 et al,2017, and DiGiacomo et al, 2023, and in poultry (Al Sulaiman et al, 2023, andAl-Garadi et al, 2023).BET has several activities that may reduce the impact of HS on cattle and improve its performance. Initially, BET is a modified amino acid composed of glycine with three methyl groups that acts as a methyl donor in many metabolic pathways (NCBI, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In ruminants, GAA supplementation increases the apparent digestibility of DMI, OM, CP, NDF and ADF (Liu & Chen et al., 2021; Li et al., 2020). In addition, betaine supplementation is associated with increased apparent digestibility of DMI, OM and CP in fattened cattle as well as significantly increased apparent digestibility of nutrients in goats (Wafaa & Reham, 2023; Wang et al., 2020). In the present study, we found that GAA and RPB supplementation improved the apparent digestibility of EE and phosphorus in the first and second parts of the experiment, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Glycine betaine is one of the most widely distributed betaines in nature; it can be synthesized by choline dehydrogenase and betaine aldehyde dehydrogenase catalyzed by the body and can also be obtained from the diet, in foods such as spinach, wheat bran, shrimp, and amaranth seeds [ 34 ]. Several studies have reported that glycine betaine plays an important role in osmolarity regulation, alongside nutritional and health issues [ 35 , 36 ]; it also has a protective role in a variety of pathologies, including several liver diseases, cancer, hemophilia, and aging [ 37 ]. In choline metabolism, choline is first oxidized by choline oxidase to betaine aldehyde, which is further oxidized to betaine; then, betaine is sequentially demethylated to form dimethylglycine, sarcosine, and glycine, which are associated with anti-inflammatory properties and immune regulation [ 38 ].…”
Section: Discussionmentioning
confidence: 99%